2014
DOI: 10.1016/j.proeng.2014.12.393
|View full text |Cite
|
Sign up to set email alerts
|

Methoding and Simulation of LM 6 Sand Casting for Defect Minimization with its Experimental Validation

Abstract: The solidification of metals continues to be a phenomenon of great interest to physicists, metallurgists, casting engineers and software developers. It directly affects the production cycle time, internal quality of castings and material utilization (yield). The process of casting solidification is complex in nature and the simulation of such process is required in industry before it is actually undertaken. The volumetric contraction accompanying solidification of molten metal manifests in defects like shrinka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…C. M. Choudhari (2014) have used LM6 for this simulation because it is suitable for sand casting. It is corrosion resistant and has greater strength and highly ductile in nature.…”
Section: Aluminiummentioning
confidence: 99%
See 1 more Smart Citation
“…C. M. Choudhari (2014) have used LM6 for this simulation because it is suitable for sand casting. It is corrosion resistant and has greater strength and highly ductile in nature.…”
Section: Aluminiummentioning
confidence: 99%
“…C. M. Choudhari (2014) simulated and compared the results of the LM 6 aluminium alloy by using AutoCAST-X software. This material has been used for casting material.…”
Section: Aluminiummentioning
confidence: 99%
“…This study showed that simulation can be effective for identification of location for occurrence of casting defect as it does not involve any wastage of material or labour. The simulation results were compared with experimental results and it was found that the analysis optimized the design of feeder by improvement in yield by 20% [13]. K M Maneesh et al have described a way to minimize the health hazards in industry to make the work condition more effective and to improve poor quality and productivity of industry by minimizing casting defects.…”
Section: Fig1 Metal Casting Processmentioning
confidence: 99%
“…Efforts have been made in the past to obtain high-quality defect-free castings by developing an in-depth understanding of the areas such as (a) design of runner and gating systems, 3240 (b) design of feeding systems (locations and number of risers), 4145 (c) filling and solidification during different casting processes, 4650 (d) casting process parameters (thermo-physical data, injection parameters, etc. ), 5054 (e) stress distribution in cast products, 55–59 and (f) quality control and assurance of the cast products.…”
Section: Case Studies Using Casting Simulation Toolsmentioning
confidence: 99%
“…In one study, Choudhari et al 43 demonstrated the shrinkage defect elimination in stepped plate casting using AutoCAST-X software followed by experimental validation. This software uses gradient vector method to calculate the temperature gradients (feed metal paths) inside the casting.…”
Section: Case Studies Using Casting Simulation Toolsmentioning
confidence: 99%